PENGARUH KONSENTRASI HIDROGEN PEROKSIDA DAN WAKTU PROSES BLEACHING TERHADAP KARAKTERISTIK SELULOSA SERAT SABUT KELAPA (Cocos nucifera L.) - Andari, I Gusti Agung Ayu Utami; Arnata, I Wayan; Dewi Anggreni, Anak Agung Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 3 (2022): SeptemberDO - 10.24843/JRMA.2022.v10.i03.p01, 2022)
Indonesia is the largest coconut producing country in the world. The abundant potential of coco fiber has not been fully utilized optimally. The purpose of this study was to determine the effect of hydrogen peroxide concentration and time of the bleaching process on the cellulose’s characteristics of coconut fiber, as well as to determine the concentration of hydrogen peroxide and time of the bleaching process to produce cellulose from coconut fiber with the best characteristics. This study used a factorial Randomized Block Design with two treatment factors, namely the concentration of H 2 O 2  (K) (20%, 30% and 40%) and the bleaching process time (W) (60 minutes and 120 minutes). Variables observed were yield, degree of whiteness, cellulose, hemicellulose and lignin. The concentration of hydrogen peroxide and the time of the bleaching process affect the yield, whiteness, cellulose, hemicellulose and lignin on cellulose of coconut fiber. The interaction between treatments affected the degree of whiteness, cellulose, hemicellulose, and lignin but had no effect on the yield of the bleached coconut fiber. The best treatment in the bleaching process to produce cellulose from coco fiber is the combination of 40% hydrogen peroxide concentration and 120 minutes of bleaching time. The cellulose characteristics of coco fiber produced were yield, whiteness, cellulose, hemicellulose and lignin is 38.45±2.51%, 76.23±1.54%, 90.19±0.66 %, 5.53±0.58%, and 3.66±0.18%, respectively.